President McPhee on his Alumni Tour of Northern California (1953)
President McPhee prepares to tour Pan American World Airways shops near San Francisco airport on his Alumni Tour of Northern California, 1953. Cal Poly alumni (from left to right, standing): Carol Boots, Jack Aboundara, Earl Lemon, Bob Houston, Bill Jones, John Milsap, H. B. Ehrenborg, Steve Hale, Walter Washington, Clause Curtis, Joe Meyers, Perry McPheeters, and (seated) Al Diehl.